EXPLORING THE EFFECTIVENESS OF COMMUNICATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PDAM MAKASSAR (A STUDY IN SERVICE AREA IV) - Rezki Amaliah Sabar; Andi Anto Patak; Andi Hajar (International Journal of Business English and Communication, 2023)
This study aims to find out whether the communication and work environment at PDAM Makassar has been effective and also to find out whether the effectiveness of communication and work environment affects employee performance at PDAM Makassar. This research uses the qualitative descriptive method. Data collection techniques use observation checklist research instruments and interview guidelines. The subjects of this study were all employees of PDAM Makassar Service Area IV complaints unit and read meters with the number of speakers being as many as five people who were randomly selected. The data analysis used in this study is data analysis using thematic analysis. And the results of observations and interviews showed that the communication and work environment in Service Area IV of the complaints and reading meter units have been effective. Characterized by well-established communication, the message you want to convey can be conveyed well to the interlocutor, as well as the creation of a comfortable work environment for employees to carry out work, work support facilities are adequate so that work can be carried out properly. So the effectiveness of communication and the work environment affects the improvement of employee performance at PDAM Makassar